1990
DOI: 10.1002/jsfa.2740500208
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality evaluation of newly developed high‐protein genotypes of pigeonpea (Cajanus cajan)

Abstract: Two high-protein genotypes of pigeonpea (Cajanus cajan L ) , H P L 8 and H P L 40, were analysed for their nutritional quality characteristics, and the results were compared with those of normal-protein genotypes (C 11 and ZCPL 211). The protein content of the high-protein genotypes was higher on average by nearly 20% but their starch content, the principal constituent of the seed, was lower by about 8 %. The higher @action (about 7%) of globulin, the major storage protein, was associated with a lower gluteli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 14 publications
0
28
1
Order By: Relevance
“…Okomoda, Tiamiyu, & Uma () stated earlier that the nutritional content of a plant is variable and depends upon the plant strain, environmental factors, and processing method applied to inactivate the anti‐nutritional factors in the seeds. This possibly explains the differences between the nutritional profile result reported in this study and those reported by Salunkhe, Chavan, and Kadam (), Tangtaweewipat and Elliott (), Singh, Jambunathan, Saxena, and Subrahmanyam (), Obasa, Dada, and Alegbeleye () and Onwuka (). The amino acid composition of soybeans was generally higher that those observed in C. cajan ; however, cysteine was substantial higher in C. cajan, and the values recorded in histidine, proline and serine were comparable ( p ≤ .05).…”
Section: Discussioncontrasting
confidence: 85%
“…Okomoda, Tiamiyu, & Uma () stated earlier that the nutritional content of a plant is variable and depends upon the plant strain, environmental factors, and processing method applied to inactivate the anti‐nutritional factors in the seeds. This possibly explains the differences between the nutritional profile result reported in this study and those reported by Salunkhe, Chavan, and Kadam (), Tangtaweewipat and Elliott (), Singh, Jambunathan, Saxena, and Subrahmanyam (), Obasa, Dada, and Alegbeleye () and Onwuka (). The amino acid composition of soybeans was generally higher that those observed in C. cajan ; however, cysteine was substantial higher in C. cajan, and the values recorded in histidine, proline and serine were comparable ( p ≤ .05).…”
Section: Discussioncontrasting
confidence: 85%
“…The results of rat feeding trials of these high-protein lines showed that boiled dal was comparable to the control in true protein digestibility, biological value, and net protein utilization [21]. They further concluded that the high-protein lines were nutritionally superior to normalprotein cultivars as the former contain quantitatively more utilizable protein and sulfur containing amino acids.…”
Section: Genetic Enhancement Of Protein Contentmentioning
confidence: 93%
“…Singh [21] assessed these high protein lines for their chemical composition. They reported large differences between the levels of protein in high-protein (28.7 to 31.1%) lines and control cultivars (23.1 to 24.8%).…”
Section: Nutritional Value Of Split Peas (Dal)mentioning
confidence: 99%
“…It was estimated that 350-450 kg protein can be harvested by growing these high protein selections on a one hectare plot. These lines on average yielded 100 kg ha −1 additional protein The increased nutritive value of this material [131] is important since pigeon pea is predominantly cultivated and consumed locally by resource poor farmers. Limited rat feeding trials to evaluate the nutritive value of cooked and raw pigeon pea samples of high and low protein genotypes showed that the high protein genotypes were superior to controls by providing more utilizable protein [129].…”
Section: High Proteinmentioning
confidence: 99%